The Guardians of the Welfare State: Universal Credit, Welfare Control and the Moral Economy of Frontline Work in Austerity Britain. (April 2021) - Koch, Insa
Ongoing processes of 'austerity localism', including the state's withdrawal from local communities, have created heightened pressures at the frontline. Sitting in local authorities, third sector bodies and community organisations, frontline workers come to act as the de facto guardians of a much-diminished welfare state. Yet, in a situation where needs outweigh resources, they also allocate support based on moral hierarchies of deservingness. This Janus-faced role of frontline workers as both a bulwark against, and an enabler of, neo-liberal welfare control is examined through the framework of a moral economy of frontline work. I argue that the tensions reflect a deeper struggle over competing notions of citizenship, and of the state's responsibilities towards its citizens, in austerity Britain today.